1998
DOI: 10.1099/00221287-144-11-3181
|View full text |Cite
|
Sign up to set email alerts
|

Molecular constituents of the replication apparatus in the plasmodium of Physarum polycephalum: identification by photoaffinity labelling

Abstract: The plasmodium of Physarum polycephalum has long been considered a model system for syncytically growing cells, but important details of the DNA replication apparatus, such as the DNA polymerase E and other replication factors, have not been detected. In this study, a new variation of photoaffinity labelling and immunoblotting was used to detect DNA polymerases and other factors in nuclear extracts of P. polycaphalum. Proteins were specifically cross-l inked with photoreactive arylazido-dCMP residues incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…In previous analytical and preparative experiments, it has been shown that PMLA was the constituent that specifically inhibited replicative DNA polymerases in nuclear extracts [1,2,7]. In the present study, we measured the inhibitory activity of PMLA using purified DNA polymerase α of P. polycephalum as an added reporter.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In previous analytical and preparative experiments, it has been shown that PMLA was the constituent that specifically inhibited replicative DNA polymerases in nuclear extracts [1,2,7]. In the present study, we measured the inhibitory activity of PMLA using purified DNA polymerase α of P. polycephalum as an added reporter.…”
Section: Resultsmentioning
confidence: 91%
“…Labeling of DNA polymerases was carried out in a 20‐µL solution containing 5 µL nuclear extract, 3–5 µ m [ 32 P]dATP (3000 Ci·mmol −1 ), 125 µ m AFBdCTP, 33 µ m of each dGTP and dTTP, 50 m m 3‐( N ‐morpholino)propanesulfonic acid buffer (pH 7.5), 50 m m KCl, 10 m m MgCl 2 , 3 m m EDTA and 5 µg activated salmon testis DNA [7]. Escherichia coli DNA polymerase I served as a positive control in a parallel, but otherwise identical, reaction mixture.…”
Section: Methodsmentioning
confidence: 99%
“…Such approach was successfully applied for investigation of the relationships among DNA polymerases and auxiliary proteins as well as DNA-interaction proteins and DNA in reconstituted systems [12][13][14][15][16] and in nuclear/cellular extracts [17][18][19]. The TLS-system is very complex and dynamic to be studied by X-ray analysis or other instrumental techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Several of such dNTP analogues were shown to be substrates of viral, prokaryotic and eukaryotic DNA polymerases [17,[21][22][23][24][25][26][27] and potentially can be introduced by TLS polymerases. Photochemical properties of the photoreactive groups have been adjusted for using excitation near UV light to avoid stimulation of the intrinsic photoreactivity of the nucleic acids and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…It creates serious problems at the stage of purification and sequencing the crosslinked peptides by the Edman procedure or by MALDI mass-spectroscopy. Low crosslinking efficiency of arylazido derivatives of nucleic acids results in poor identification of DNA polymerases or accompanied proteins in the crude cellular or nuclear extracts (6). Therefore future application of photoaffinity labeling technique to study replication machinery demands improved efficiency and specificity of photoaffinity labeling of DNA polymerases.…”
mentioning
confidence: 99%